2007
DOI: 10.1002/art.22845
|View full text |Cite
|
Sign up to set email alerts
|

Association of smoking with the constitution of the anti–cyclic citrullinated peptide response in the absence of HLA–DRB1 shared epitope alleles

Abstract: Objective. Smoking is a risk factor for anti-cyclic citrullinated peptide (anti-CCP) antibody-positive rheumatoid arthritis (RA) in patients with HLA-DRB1 shared epitope (SE) alleles. It is unknown whether smoking influences not only the presence of these antibodies, but also other characteristics of the anti-CCP response, such as isotype usage. The aim of this study was to determine the influence of smoking on anti-CCP isotypes in RA patients, and to determine whether this influence is observed in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 12 publications
2
24
0
1
Order By: Relevance
“…The numbers were however not large enough to draw any firm conclusions, although the findings are in line with data from Verpoort [82]. Further, Kokkonen and colleagues showed that smoking pre-RA patients developed circulating IgA-CCP earlier than their non-smoking counterparts [97].…”
Section: Smoking and Iga Anti-ccp In Serumsupporting
confidence: 50%
See 1 more Smart Citation
“…The numbers were however not large enough to draw any firm conclusions, although the findings are in line with data from Verpoort [82]. Further, Kokkonen and colleagues showed that smoking pre-RA patients developed circulating IgA-CCP earlier than their non-smoking counterparts [97].…”
Section: Smoking and Iga Anti-ccp In Serumsupporting
confidence: 50%
“…Smoking has also been found to induce inflammation [78], and to associate with a number of autoimmune diseases [79][80][81][82][83]. However, components of cigarette smoke, e. g. nicotine, have also been shown to have immunosuppressive/anti-inflammatory effects [84,85].…”
Section: Environmental Triggersmentioning
confidence: 99%
“…For instance, it is well established that a combination of cigarette smoking and genetic carriage of HLA-DRB1/SE is a strong risk of developing IgG-ACPA positive, but not IgG-ACPA negative, RA (Morgan et al 2009;Padyukov et al 2011). Although derived from studies of much smaller format, there are indications of serum IgA-ACPA being even more strongly related to smoking but not to SE (Verpoort et al 2007;Svärd et al 2010) and Kokkonen et al showed that smoking pre-RA patients developed circulating IgA-CCP earlier than did their non-smoking counterparts (Kokkonen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the best documented ACPA test for clinical routine is IgG antibodies against the 'second generation' of cyclic citrullinated peptides (CCP). In a subset of IgG-ACPA positive patients circulating IgA-ACPA have been described, but the low sensitivity limits its diagnostic value (Verpoort et al 2006;Verpoort et al 2007;Svärd et al 2008;Svärd et al 2010). The prognostic value of serum IgA-ACPA has not been firmly established, but similar to rheumatoid factor (RF) of IgA-class (Houssien et al 1997;Lindqvist et al 2005;Berglin et al 2006), a more severe disease has been described in IgA-ACPA positive patients (Verpoort et al 2006;Verpoort et al 2007;Svärd et al 2008;Svärd et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a geneenvironment interaction between the shared epitope and smoking in ACPAϩ, but not ACPA-, RA has been reported in northern European RA patient cohorts (8,9). On the other hand, however, the association of the specific HLA-DRB1 alleles with ACPAϩ RA appears to vary between different populations (10)(11)(12), and the specific gene-environment interaction in ACPAϩ RA could not be confirmed in all studies (13,14).…”
mentioning
confidence: 96%